ANALYSIS OF MUTATIONS IN KRAS AND BRAF GENES IN COLORECTAL CANCER IN RUSSIAN PATIENTS - E. E. Pisareva; L. N. Ljubchenko; S. P. Kovalenko; V. A. Shamanin (Сибирский онкологический журнал, 2016)
Mutations in KRAS and BRAF genes in 80 colorectal cancer (CRC) samples from Russian patients were tested using two methods: 1) allele-specific real-time PCR (as-rt PCR) and 2) wild-type blocking PCR with Sanger sequencing (WTBS). Material and methods. Sections of fresh frozen or formalin-fixed paraffin embedded tumor tissue from 80 patients were used in the study. Tumor tissue content was determined on H&E stained sections. Samples were first tested by as-rtPCR for common mutations of the KRAS gene (G12C, G12S, G12R, G12V, G12D, G12A, G13D) and mutations BRAFV600E. After that samples were evaluated in PCR with oligonucleotide blocking amplification of wild-type DNA for enrichment with mutant allele followed by Sanger sequencing of the PCR DNA (WTBS method). Results. In 5 (6.3 %) cases samples had low tumor tissue content (<20 %). In reconstruction experiments both methods detected 1–5 % mutant allele. Mutations of KRAS and BRAF genes were found in 37 (46 %) and 3 (3.8 %) of the clinical cases, respectively. Classification in to wild-type and mutant samples by both methods was in agreement in 79 (98.8 %) cases. A single case with rare mutation KRASG13R was detected by WTBS, but was missed by as-rtPCR since this mutation is not included in the test. Of note, KRAS mutations were detected by both tests in two cases with low tumor content. Two cases were found with multiple mutations: one with KRASG12V and G13D, and one with KRASG13D and BRAFV600E. Conclusion. The frequency of mutations in CRC was 46 % for mutations in the KRAS gene, and 3.8 % for the BRAF. We showed 98.8% agreement in KRAS mutation detection by sensitive Sanger sequencing and as-rt PCR. The data on the frequencies of mutations are in agreement with studies in other countries. This in the first study to discover CRC case with multiple mutations KRASG13D and BRAFV600E.